2016
DOI: 10.4028/www.scientific.net/msf.856.190
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Influence of the Electromagnetic Field in the Vicinity of High Voltage Overhead Line

Abstract: The magnetic and electrical field in the vicinity of overhead power line for high voltage - 220 kV is investigated. FEM model is created. Simulations of normal and emergency mode of the power line are made. The electrical intensity at idle mode in some areas, close to overhead power line, creates a high voltage level for humans. It can create also disturbances in the electrical equipment and the vehicles. These surges violate electromagnetic compatibility. The magnetic induction at emergency mode – short circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…will supply lines, transformers and Load are equivalent to impedance, as a basis for the establishment of frequency communication signal modulation and transmission model, through simulation [3]. It is shown that when the modulation is made at 30 before the zero crossing of the voltage, the main component of the distortion signal is in the vicinity of the voltage zero to about 3ms, the frequency between 200Hz to 600Hz, the amplitude of the distortion signal and the modulation transformer Capacity and modulation device parameters, when the distribution network load is heavy, the modulation signal will exist residual oscillation section [3,4].…”
Section: Related Workmentioning
confidence: 99%
“…will supply lines, transformers and Load are equivalent to impedance, as a basis for the establishment of frequency communication signal modulation and transmission model, through simulation [3]. It is shown that when the modulation is made at 30 before the zero crossing of the voltage, the main component of the distortion signal is in the vicinity of the voltage zero to about 3ms, the frequency between 200Hz to 600Hz, the amplitude of the distortion signal and the modulation transformer Capacity and modulation device parameters, when the distribution network load is heavy, the modulation signal will exist residual oscillation section [3,4].…”
Section: Related Workmentioning
confidence: 99%